Role of MicroRNAs in Renin-Angiotensin-Aldosterone System-Mediated Cardiovascular Inflammation and Remodeling - Maricica Pacurari; Paul B. Tchounwou (Hindawi Limited, 2015)
MicroRNAs are endogenous regulators of gene expression either by inhibiting translation or protein degradation. Recent studies indicate that microRNAs play a role in cardiovascular disease and renin-angiotensin-aldosterone system- (RAAS-) mediated cardiovascular inflammation, either as mediators or being targeted by RAAS pharmacological inhibitors. The exact role(s) of microRNAs in RAAS-mediated cardiovascular inflammation and remodeling is/are still in early stage of investigation. However, few microRNAs have been shown to play a role in RAAS signaling, particularly miR-155, miR-146a/b, miR-132/122, and miR-483-3p. Identification of specific microRNAs and their targets and elucidating microRNA-regulated mechanisms associated RAS-mediated cardiovascular inflammation and remodeling might lead to the development of novel pharmacological strategies to target RAAS-mediated vascular pathologies. This paper reviews microRNAs role in inflammatory factors mediating cardiovascular inflammation and RAAS genes and the effect of RAAS pharmacological inhibition on microRNAs and the resolution of RAAS-mediated cardiovascular inflammation and remodeling. Also, this paper discusses the advances on microRNAs-based therapeutic approaches that may be important in targeting RAAS signaling.